Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1186/1471-2334-9-122
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis ecology in Venezuela: epidemiologic correlates of common spoligotypes and a large clonal cluster defined by MIRU-VNTR-24

Abstract: BackgroundTuberculosis remains an endemic public health problem, but the ecology of the TB strains prevalent, and their transmission, can vary by country and by region. We sought to investigate the prevalence of Mycobacterium tuberculosis strains in different regions of Venezuela. A previous study identified the most prevalent strains in Venezuela but did not show geographical distribution nor identify clonal genotypes. To better understand local strain ecology, we used spoligotyping to analyze 1298 M. tubercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 38 publications
4
25
2
Order By: Relevance
“…In contrast to previous reports from Latin America in which LAM was the most common family (11,(36)(37)(38)(39)(40), our results demonstrated a predominance of the Haarlem family among new cases in the district of San Juan de Lurigancho.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast to previous reports from Latin America in which LAM was the most common family (11,(36)(37)(38)(39)(40), our results demonstrated a predominance of the Haarlem family among new cases in the district of San Juan de Lurigancho.…”
Section: Discussioncontrasting
confidence: 56%
“…In a molecular analysis of M. tuberculosis DNA from a family of 18th century Hungarians two spoligotypes were identified, corresponding to SIT50 and SIT53 [25]. As in our study SIT53 is found in elderly patients in other parts of the world: in a study from Venezuela, patients with SIT53 had a significantly higher mean age compared to all other patients [26], and in Mexico SIT53 was significantly more prevalent in elderly patients, especially in females [27]. Polymorphism in the direct repeat region in clinical isolates appears to be the result of successive deletions of single discrete direct variant repeats (DVRs) or of multiple contiguous DVRs from a primordial direct repeat region [28].…”
Section: Discussionsupporting
confidence: 77%
“…This sublineage, although described for the first time in 1998 in this Colombian seaport city, has only been reported since then from patients whose origin is from this same city, or patients with the same origin but diagnosed in the country's inland major urban settings [38]–[40]. In agreement with these data, despite the human migration from Asia, where the Beijing isolates are very frequent, they represent a proportion about 5% or less of isolates in Latin America, according to several reports [20][25].…”
Section: Discussionmentioning
confidence: 61%